A Range Doppler Imaging Algorithm Based on the MSR Spectrum for the Multi-Aperutre Syntactic Sonar. Issue 4 (March 2020) - Lv, Jinhua; Tang, Jinsong; Wu, Haoran
Abstract: For ignoring the azimuth variation of the "non-hop-go-hop" time, the existing imaging algorithm for multi-aperture have a poor imaging in moderate squint, so this paper proposes a multi-aperture range Doppler imaging algorithm based on the spectrum of method of series reversion. The exact range history is approximated once, and the error can be adjusted by the order of Taylor series expansion. Then, the analytical expression of the two-dimensional spectrum is obtained by the method of series reversion. In signal processing, the signal of the single aperture is handle with the squint range Doppler imaging algorithm, and the azimuth spectrum is superposed to each aperture, to obtain the image. Finally, the effectiveness and correctness of the algorithm is provided by the simulation experiments.